Cardiovascular assessment of patients with Ullrich-Turner's Syndrome on Doppler echocardiography and magnetic resonance imaging - Castro,Ana Valéria Barros de (2002)
OBJECTIVE: To assess the cardiovascular features of Ullrich-Turner's syndrome using echocardiography and magnetic resonance imaging, and to correlate them with the phenotype and karyotype of the patients. The diagnostic concordance between the 2 methods was also assessed. METHODS: Fifteen patients with the syndrome were assessed by echocardiography and magnetic resonance imaging (cardiac chambers, valves, and aorta). Their ages ranged from 10 to 28 (mean of 16.7) years. The karyotype was analyzed in 11 or 25 metaphases of peripheral blood lymphocytes, or both. RESULTS: The most common phenotypic changes were short stature and spontaneous absence of puberal development (100%); 1 patient had a cardiac murmur. The karyotypes detected were as follows: 45,X (n=7), mosaics (n=5), and deletions (n=3). No echocardiographic changes were observed. In regard to magnetic resonance imaging, coarctation and dilation of the aorta were found in 1 patient, and isolated dilation of the aorta was found in 4 patients. CONCLUSION: The frequencies of coarctation and dilation of the aorta detected on magnetic resonance imaging were similar to those reported in the literature (5.5% to 20%, and 6.3% to 29%, respectively). This confirmed the adjuvant role of magnetic resonance imaging to Doppler echocardiography for diagnosing cardiovascular alterations in patients with Ullrich-Turner's syndrome.